Characterization of agave bagasse as a function of ionic liquid pretreatment. (April 2015) - Perez-Pimienta, Jose A.; Lopez-Ortega, Monica G.; Chavez-Carvayar, Jose A.; Varanasi, Patanjali; Stavila, Vitalie; Cheng, Gang; Singh, Seema; Simmons, Blake A.
Abstract: Previous studies of agave bagasse (AGB-byproduct of tequila industry) presented unidentified crystalline peaks that are not typical from common biofuel feedstocks (e.g. sugarcane bagasse, switchgrass or corn stover) making it an important issue to be addressed for future biorefinery applications. Ionic liquid (IL) pretreatment of AGB was performed using 1-ethyl-3-methylimidazolium acetate ([C2 mim][OAc]) at 120, 140 and 160 °C for 3 h and a mass fraction of 3% in order to identify these peaks. Pretreated samples were analyzed by powder X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, field emission scanning electronic microscopy (FE-SEM), thermal analysis (TGA-DSC) and wet chemistry methods. Previous unidentified XRD peaks on AGB at 2θ = 15°, 24.5° and 30.5°, were found to correspond to calcium oxalate (CaC2 O4 ) in a monohydrated form. IL pretreatment with [C2 mim][OAc] was observed to remove CaC2 O4 and decrease cellulose crystallinity. At 140 °C, IL pretreatment significantly enhances enzymatic kinetics and leads to ∼8 times increase in sugar yield (6.66 kg m −3 ) when compared to the untreated samples (960 g m −3 ). These results indicate that IL pretreatment can effectively process lignocellulosic biomass with high levels of CaC2 O4 . Highlights: Chemical behavior of agave bagasse pretreated by ionic liquid (IL) is assessed. Previously unidentified XRD peaks correspond to calcium oxalate (CaC2 O4 ). Total sugar yield and initial enzymatic hydrolysis rate were higher at 140 °C. IL pretreatment can effectively process biomass with high levels of CaC2 O4. Increasing the temperature of IL pretreatment causes the agglomeration of CaC2 O4 .